Lazatto Website UI/UX Optimization: Improve Usability Through User Centered Design - Hidayah, Delely Rahmawati (Deparment Information System, Siliwangi University, 2024)
Improving the UI/UX quality of Lazatto's website is important given the role of digital interfaces in attracting and retaining customers in the modern era. Lazatto, as a fast food brand, faces challenges in interface design, such as unintuitive navigation and lack of satisfying user experience, which could potentially reduce its competitiveness. Therefore, the User Centered Design (UCD) method was chosen to address these issues due to its focus on putting the user's needs and experience as the top priority. The method involves several stages, namely user needs analysis, wireframe and prototype-based solution design, and iterative evaluation through live user testing. The implementation resulted in a new design with five main features. Based on usability testing involving six different scenarios, the highest Usability Score was obtained in scenario 1 with a score of 4.27, signifying user success and a clear interface, while scenario 2 recorded the lowest score (3.89) due to challenges with visual clarity. The average scenario completion time was consistent at 3.85 with a high average visual clarity across all scenarios, indicating that the interface was generally perceived as clear by users. These optimization results confirm the importance of UCD implementation in improving user experience while also providing. Keywords— Lazatto, UI/UX, User Centered Design